2013
DOI: 10.1177/1461444813516832
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates’ attitudes to text messaging language use and intrusions of textisms into formal writing

Abstract: Students’ increasing use of text messaging language has prompted concern that textisms (e.g., 2 for to, dont for don’t, ☺) will intrude into their formal written work. Eighty-six Australian and 150 Canadian undergraduates were asked to rate the appropriateness of textism use in various situations. Students distinguished between the appropriateness of using textisms in different writing modalities and to different recipients, rating textism use as inappropriate in formal exams and assignments, but appropriate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…These results converge with those of previous researchers who have found that undergraduates consider it less appropriate to use textisms when writing to instructors than to friends (Drouin & Davis, 2009) and in more formal than less formal writing and messaging contexts (Grace et al, 2013). Our results are also in line with those of Lewandowski and Harrington (2006), who found that undergraduates formed more negative views of other students who used textisms when writing to professors than those who wrote in standard English.…”
Section: Discussionsupporting
confidence: 92%
“…These results converge with those of previous researchers who have found that undergraduates consider it less appropriate to use textisms when writing to instructors than to friends (Drouin & Davis, 2009) and in more formal than less formal writing and messaging contexts (Grace et al, 2013). Our results are also in line with those of Lewandowski and Harrington (2006), who found that undergraduates formed more negative views of other students who used textisms when writing to professors than those who wrote in standard English.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies (Drouin and Davis 2009;Grace et al 2015) showed that the use of textisms (including smileys, LOL, haha etc.) is mainly reserved for causal text messages and considered to be inappropriate in formal writing.…”
Section: Degree Of Involvementmentioning
confidence: 99%
“…This type of informal written communication is referred to as SMS language or textese (Aziz et al 2013;Grace et al 2015).…”
Section: Sms Languagementioning
confidence: 99%
“…The reason for that evolution matters as much as reliance on abbreviations is that a number of scholars have argued that the growing prevalence of SMS language may impact how people (and students in particular) use and understand standard English, especially in formal written settings like academic assignments (Verheijen 2013; Grace et al 2015). However, scholars and popular commentators are divided on the specifics of this hypothetical effect, including basic points such as whether it is likely to be positive or negative.…”
Section: Sms Language and Standard Englishmentioning
confidence: 99%
See 1 more Smart Citation